Discovery of Potent and Selective 7-Azaindole Isoindolinone-Based PI3Kγ Inhibitors - Miles, Dillon H. (ACS Med Chem Lett, 2020)
[Image: see text] The successful application of immunotherapy in the treatment of cancer relies on effective engagement of immune cells in the tumor microenvironment. Phosphoinositide 3-kinase γ (PI3Kγ) is highly expressed in tumor-associated macrophages, and its expression levels are associated with tumor immunosuppression and growth. Selective inhibition of PI3Kγ offers a promising strategy in immuno-oncology, which has led to the development of numerous potent PI3Kγ inhibitors with variable selectivity profiles. To facilitate further investigation of the therapeutic potential of PI3Kγ inhibition, we required a potent and PI3Kγ-selective tool compound with sufficient metabolic stability for use in future in vivo studies. Herein, we describe some of our efforts to realize this goal through the systematic study of SARs within a series of 7-azaindole-based PI3Kγ inhibitors. The large volume of data generated from this study helped guide our subsequent lead optimization efforts and will inform further development of PI3Kγ-selective inhibitors for use in immunomodulation.